The impact of the donors’ COVID-19 status on the outcomes of allogeneic hematopoietic stem cell transplantation: a multi-center retrospective study - Huang, Yifei; Fan, Zhiping; Hu, Yingying; Feng, Sizhou; Wang, Shunqing; Zhang, Shanyu; Huang, Fen; Xuan, Li; Xu, Na; Liu, Hui; Wang, Zhixiang; Sun, Jing; et al. (Frontiers in Microbiology, 2024)
Introduction To explore the impact of donors’ COVID-19 status on allogeneic stem cell transplantation (allo-HSCT), we compared the transplant outcomes of 74 participants. Methods This multi-center retrospective study included nine participants receiving grafts from COVID-19 positive donors (CPD), 45 from COVID-19 experienced donors (CED), and 20 from COVID-19 naive donors (CND). We evaluated engraftment, complications, and survival rates among the three groups. Results All apheresis procedures were successful with no significant differences in CD34+ cells or lymphocytes in grafts among the three groups. All patients achieved engraftment by day 30 post-HSCT. The incidence of grade II-IV acute graft-versus-host disease (aGVHD) was 55.6%, 20%, and 10% in the CPD, CED, and CND groups, respectively (p = 0.024). Multivariate analysis indicated that COVID-19 positivity in donors at the time of apheresis was an independent risk factor for II-IV aGVHD (p = 0.020, OR = 12.159, 95% CI 1.783 -135.760). No differences were observed among the groups in terms of chronic GVHD, viral infection, or sinusoidal obstruction syndrome. The 6-month overall survival and disease-free survival rates were also similar among the three groups. Discussion Our results suggest that the COVID-19-positive status of donors might not impact graft collection, engraftment, or short-term survival of allo-HSCT recipients but might increase the risk of aGVHD. Further research is needed to explore the influence of donors’ COVID-19 status on long-term complications and survival in allo-HSCT recipients.